Reducing surgery in management of spontaneous abortions. Family physicians can make a difference. - Wiebe, E. (College of Family Physicians of Canada, 1999)
OBJECTIVE: To test the effectiveness of physician and patient education in reducing the rate of surgery in management of spontaneous abortions in family practice. DESIGN: A before-after intervention trial. SETTING: Urban and suburban family doctors' practices in greater Vancouver, BC. PARTICIPANTS: Family practice patients (56 physicians contributed 417 patients) who had spontaneous abortions between June 1997 and August 1998. INTERVENTIONS: Seminars for doctors and educational pamphlets for patients. MAIN OUTCOME MEASURES: Rate of surgeries, and rates of referrals and complications. RESULTS: In the 2 years before the intervention, the rate of surgery was 45.8% (n = 299); after, it was 32.2% (n = 118). No transfusions were required. Before the intervention, 17% of women had hemorrhages; after, 13%. Rates of infection were 3.7% and 0.8%, respectively. Rates of referral to gynecologists were 54.0% and 40.2%, respectively. CONCLUSIONS: Patients of family doctors who attended seminars and agreed to join the study had significantly reduced rates of surgery after spontaneous abortions. Rates of referral for these patients were also lower, and there was no increase in complications.